Opacity, Credit Rating Shopping, and Bias - Sangiorgi, Francesco; Spatt, Chester (Management Science, 2017)
We develop a rational expectations model in which an issuer purchases credit ratings sequentially, deciding which to disclose to investors. Opacity about contacts between the issuer and rating agencies induces potential asymmetric information about which ratings the issuer obtained. While the equilibrium forces disclosure of ratings when the market knows these have been generated, endogenous uncertainty about whether there are undisclosed ratings can arise and lead to selective disclosure and rating bias. Although investors account for this bias in pricing, selective disclosure makes ratings noisier signals of project value, leading to inefficient investment decisions. Our paper suggests that regulatory disclosure requirements are welfare enhancing. This paper was accepted by Gustavo Manso, finance.